DIGITAL INNOVATIONS AND INVESTMENTS: DRIVING SUSTAINABLE DEVELOPMENT IN UZBEKISTAN’S DIGITAL MANAGEMENT SECTOR - Khairulla Fayzullaevich Sattarov (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This scientific work analyzes the role of digital management in Uzbekistan in the sustainable development of entrepreneurship, focusing on the roles of innovations and investments. The study explores key issues such as enhancing competitiveness, effectively utilizing digital technologies, and attracting both domestic and foreign investments to achieve sustainable development in digital management systems. Moreover, the research emphasizes the significance of human capital development, digital literacy, and continuous professional training in ensuring the effective implementation of digital strategies. The findings suggest that a comprehensive and well-coordinated approach to digital management can significantly contribute to economic growth, increase productivity, and enhance the global competitiveness of Uzbekistan.